2018
DOI: 10.1002/jbmr.3562
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Kidney Disease Is Associated With Greater Bone Marrow Adiposity

Abstract: Bone marrow adiposity is associated with aging, osteoporosis, and reduced hematopoiesis, as well as anorexia nervosa, but little is known about the underlying mechanisms that affect marrow adiposity. Chronic kidney disease (CKD) may influence bone marrow adipose tissue (BMAT), possibly through loss of lean mass or higher circulating levels of sclerostin. To test these hypotheses, we investigated the cross-sectional association between estimated glomerular filtration rate (eGFR) as a measure of kidney function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 29 publications
3
30
2
1
Order By: Relevance
“…(1) Higher circulating levels of sclerostin has also been suggested to play a role in the relationship between CKD and greater bone marrow adiposity. (10) Of note, several lines of evidence have shown that physical inactivity can result in higher circulating levels of sclerostin (11) and greater bone marrow adiposity, (12) which reasonably supports the above-mentioned theory that poor vitamin K status reflects physical inactivity and can be regarded as an indirect indicator of hip fragility in CKD.…”
Section: To the Editorsupporting
confidence: 59%
“…(1) Higher circulating levels of sclerostin has also been suggested to play a role in the relationship between CKD and greater bone marrow adiposity. (10) Of note, several lines of evidence have shown that physical inactivity can result in higher circulating levels of sclerostin (11) and greater bone marrow adiposity, (12) which reasonably supports the above-mentioned theory that poor vitamin K status reflects physical inactivity and can be regarded as an indirect indicator of hip fragility in CKD.…”
Section: To the Editorsupporting
confidence: 59%
“…In humans, similar findings in women and men are often found. For example, for both sexes there is a negative association between BMAT and BMD and a positive association between BMAT and chronic kidney disease as well as total body fat (26,31,40,41). However, differences between women and men have been found; for example, women and men have different levels of BMAT (26), and there was only an association between BMAT and serum sclerostin in men (22).…”
Section: Discussionmentioning
confidence: 99%
“…Two additional cell lines, IDG-SW3 and Ocy454, were isolated from double transgenic mice expressing green fluorescent protein (Gfp1) under the dentin matrix acidic phosphoprotein 1 (Dmp1) promoter as well as a thermolabile large T-antigen. Importantly, both cell lines resemble late osteocytes and hence express high levels of late osteocyte markers, including sclerostin (Woo et al 2011, Spatz et al 2015. Ex vivo bone explants have the advantage of allowing the study of living osteocytes within their natural setting and are particularly well suited to investigating the response to mechanical loading (Kogawa et al 2018, Morrell et al 2018.…”
Section: Osteoblast Lineagementioning
confidence: 99%
“…The BMAT depot is less well understood than BAT or WAT, and its influence on the skeleton is the subject of intense interest since its anatomical location means it is ideally placed to provide a fat-bone connection. BMAT is elevated in conditions associated with low bone mass, including osteoporosis, anorexia nervosa, ageing and chronic kidney disease (CKD) (Hardouin et al 2016, Fairfield et al 2017b, Woods et al 2018. In mice, absence of sclerostin is associated with decreased BMAT whilst Scl-Ab reduces BMAT accumulation by decreasing both adipocyte number and size (Fairfield et al 2017b).…”
Section: Adipocytesmentioning
confidence: 99%